An experimental investigation of an adsorption refrigeration system based on a silica gel-water pair - Goh, Hui Yi. (2011)
Adsorption refrigeration technology is under much research with the increasing demand to protect our environment, and also to reduce the use of Earth's resources, since it is powered by waste heat or renewable energy, and also does not require the use of environmentally harmful refrigerants.